ANALYSIS OF EMPOWERMENT OF PRODUCTIVE WAKF FUNDS THROUGH QARDUL-HASAN FINANCING IN ALPEND BAROKAH MANDIRI'S MICRO WAKAF BANK (BWM) - Argantara, Zaid Raya; Safitri, Yuliana (Filantropi : Jurnal Manajemen Zakat dan Wakaf, 2023)
The purpose of this research is to answer the problem that is focused on research is how the implementation of qordul-hasan payment in small and medium-sized micro-enterprises and the role of qordul-hasan accounts in the creation of small and medium-sized micro-enterprises at Wakaf Mikro Alpend Barokah Mandiri. The method used in this study is qualitative with qualitative approaches to phenomenology, with interview data sources, observations and documentation. Data analysis uses Janice Mc Drury's theory of studying data, finding themes, writing models, determining coding and making decisions so that we get the facts. The results of this study indicate that the implementation of these qordul-hasan accounts through the level of identification, socialisation, qualification testing, pre-PWK, PWK and Halaqah Mingguan (HALMI). The role of the qordul-hasan account provided by the Wakaf Bank Mikro Alpen Barokah Mandiri has had an impact on the expansion of the efforts carried out in the passport.